2023
DOI: 10.7717/peerj.14565
|View full text |Cite
|
Sign up to set email alerts
|

Novice assessors demonstrate good intra-rater agreement and reliability when determining pressure pain thresholds; a cross-sectional study

Abstract: Background Experienced assessors show good intra-rater reproducibility (within-session and between-session agreement and reliability) when using an algometer to determine pressure pain thresholds (PPT). However, it is unknown whether novice assessors perform equally well. This study aimed to determine within and between-session agreement and reliability of PPT measurements performed by novice assessors and explored whether these parameters differed per assessor and algometer type. Methods Ten novice assessor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
0
0
Order By: Relevance
“…A Commander digital algometer (the Commander™ console and Algometer dynamometer), which can be applied the force from 0 to 110 N, was used to monitor the PA force on each lumbar segment. Previous studies demonstrated the high reliability of measuring the force ( Kinser, Sands & Stone, 2009 ; Reezigt et al, 2023 ). The algometer and Commander console were factory calibrated and were automatically set to zero calibration when turned on.…”
Section: Methodsmentioning
confidence: 99%
“…A Commander digital algometer (the Commander™ console and Algometer dynamometer), which can be applied the force from 0 to 110 N, was used to monitor the PA force on each lumbar segment. Previous studies demonstrated the high reliability of measuring the force ( Kinser, Sands & Stone, 2009 ; Reezigt et al, 2023 ). The algometer and Commander console were factory calibrated and were automatically set to zero calibration when turned on.…”
Section: Methodsmentioning
confidence: 99%